High-capacity and fast charge storage aromatic organic material and preparation method thereof and deep-sea energy storage battery

By using tetraamnolobenzenequinone and ball milling to prepare poly(pyrazin-benzenequinone) organic electrode materials, the problem of insufficient capacity and conductivity of organic electrode materials in potassium ion batteries is solved, and high capacity and rapid charge storage is achieved, promoting The practical application of potassium ion batteries.

CN118812847BActive Publication Date: 2024-12-24SANYA SCI & EDUCATION INNOVATION PARK WUHAN UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411303655.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-24
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

In potassium ion batteries, existing organic electrode materials have problems such as low actual capacity, insufficient electronic conductivity and poor stability of organic electrolytes, and the synthesis of high-performance organic electrode materials is complex and difficult to produce on a large scale.

Method used

Using tetraaminobenzenequinone (TABQ) as synthetic monomer, poly(pyrazine-benzenequinone) (pTAPT) organic electrode material with extended conjugation structure was prepared through ball milling treatment and in-situ thermal condensation strategy to achieve high capacity and Fast charge storage.

Benefits of technology

Improve the redox site density of organic compounds, expand the conjugated framework of aromatic rings, solve the trade-off between high capacity and high conductivity, achieve high energy density and excellent cycle life, and is simple in process and costly Low, suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118812847B_ABST
    Figure CN118812847B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-capacity and fast charge storage aromatic organic material, a preparation method thereof, and a deep-sea energy storage battery. The method uses tetraaminobenzoquinone as a synthetic monomer, adds sodium chloride and stirs evenly to obtain a black mixture; the black mixture is transferred to a nylon ball mill, concentrated hydrochloric acid is added to the tank, and then ball milling is performed to obtain a mixture; the mixture is put into a dilute sulfuric acid solution and boiled, and the precipitate is washed with deionized water and ethanol after filtering, and dried at high temperature under a vacuum environment to obtain a powder; after high-temperature calcination, it is naturally cooled to room temperature to obtain a high-capacity and fast charge storage aromatic organic material. The material of the present invention is applied to potassium ion batteries, which can significantly improve their electrochemical performance. The present invention has the advantages of high cost-effectiveness, simple and environmentally friendly preparation process, wide applicability, and excellent electrochemical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrochemical technology, and in particular to a high-capacity and fast-charge storage aromatic organic material and a preparation method thereof, and a deep-sea energy storage battery. Background Art

[0002] Among many electrochemical energy storage technologies, potassium-ion batteries have become a powerful choice for distributed energy storage systems due to their advantages such as low cost and high voltage. They are also one of the most promising directions in electrochemical energy storage technology.

[0003] In the past two decades, organic materials have become the focus of research on future high-performance electrode materials due to their unique advantages. First, these materials are composed of lightweight atoms and are able to undergo multiple electron redox reactions on each monomer, thus providing high specific capacity. Second, organic compounds can be extracted from abundant biomass and synthesized by mild and cost-effective methods, which makes them environmentally sustainable and economical. Third, the chemical diversity of organic materials provides design flexibility, allowing the construction of molecular and crystal structures with ideal electrochemical and kinetic properties. In addition, these materials have flexible characteristics and highly reversible redox reactions without significant structural changes, making them very attractive in potassium ion batteries. Despite these potential advantages of organic materials, there are still some challenges, such as actual capacity far below theoretical value, low electronic conductivity, and poor stability to organic electrolytes. In addition, the synthesis of high-performance organic electrode materials usually requires multiple steps, which leads to difficulties in large-scale production, reproducibility, and purification. Therefore, it is of great significance to develop organic electrode materials with high capacity, high conductivity, excellent cycle stability, and simple, reproducible synthesis methods that are easy to mass produce.

[0004] Although the service life of organic electrode materials can be stabilized and extended by combining inactive groups to form an extended conjugated structure, it will inevitably sacrifice its actual capacity and usually result in a slow ion / electron conduction rate. There is still a trade-off between the conjugated system and energy density. Composite with superconducting carbon materials is an effective strategy to improve the electronic conductivity and electrochemical properties of organic compounds. At the same time, the weak interaction between superconducting carbon and organic materials can inhibit its dissolution in organic electrolytes. However, due to its high production cost, it is a huge challenge to achieve large-scale application, and simple mechanical mixing is difficult to make an ideal composite electrode, which further limits its application. None of the above strategies can meet the demand for high-performance organic electrode materials. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a high-capacity and fast charge storage aromatic organic material and its preparation method and deep-sea energy storage battery. The method uses tetraaminobenzoquinone (TABQ) as a synthetic monomer, combines a simple and scalable ball milling process, and then obtains an aromatic organic material with an extended conjugated structure through a subsequent in-situ thermal condensation strategy, namely a poly(pyrazine-benzoquinone) (pTAPT) organic electrode material. The modification method of the organic electrode material has a simple process and high feasibility, and can realize the large-scale production of high-capacity aromatic organic materials with fast charge storage capabilities, thereby promoting the practical application of high-performance potassium ion batteries; the organic electrode material has significant scientific value and broad practical application prospects in the application of low-cost distributed energy storage systems.

[0006] To achieve the above purpose, the technical solution designed by the present invention is as follows:

[0007] The present invention provides a method for preparing a high-capacity and fast charge storage aromatic organic material, comprising the following steps:

[0008] (1) Add tetraaminobenzoquinone and sodium chloride into an agate mortar and grind thoroughly to obtain a black mixture;

[0009] (2) adding the black mixed material into a nylon ball milling jar containing agate ball milling beads, adding concentrated hydrochloric acid, and placing the nylon ball milling jar in a planetary ball mill for ball milling to obtain a mixed material;

[0010] (3) transferring the mixture into a round-bottom flask, adding a dilute sulfuric acid solution into the round-bottom flask, heating and boiling, collecting the precipitate, washing the precipitate, and drying it under vacuum and high temperature to obtain a powder;

[0011] (4) The powder is transferred to a tube furnace, calcined at high temperature under vacuum, and cooled to room temperature to obtain a high-capacity and fast charge storage aromatic organic material.

[0012] Furthermore, in the step (1), the mass ratio of tetraaminobenzoquinone to sodium chloride is 1-5:20; and the grinding is performed for 10-20 min.

[0013] Furthermore, the mass ratio of tetraaminobenzoquinone to sodium chloride is 1:20.

[0014] Furthermore, in step (2), the mass volume ratio of the black mixture to concentrated hydrochloric acid is 21-25:2, the concentration of concentrated hydrochloric acid is 12 mol / L; the capacity of the nylon ball mill is 100 mL; the particle sizes of the agate ball mill beads are 4 mm, 5 mm, and 6 mm, respectively, and the number ratio is 3:2:1; the rotation speed of the ball milling treatment is 200-300 rpm, and the time is 10-20 min.

[0015] Furthermore, the mass volume ratio of the black mixture to concentrated hydrochloric acid is 21:2.

[0016] Furthermore, in step (3), the capacity of the round-bottom flask is 1 L, the concentration of dilute sulfuric acid is 0.01 mol / L, and the volume ratio of concentrated hydrochloric acid to dilute sulfuric acid is 1:220-250; the precipitate is washed three times with deionized water and anhydrous ethanol; and the vacuum high-temperature drying conditions are 80-90°C for 8-12 h.

[0017] Furthermore, in the step (4), the heating rate of the high temperature calcination is 5°C / min, from room temperature to 300°C, and the calcination time is 8-12 h.

[0018] The present invention also provides a high-capacity and fast charge storage aromatic organic material prepared by the preparation method, characterized in that the high-capacity and fast charge storage aromatic organic material uses tetraaminobenzoquinone as a synthetic monomer, combined with ball milling treatment, and then is made through a subsequent in-situ thermal condensation strategy.

[0019] The present invention also provides a negative electrode sheet for a deep-sea energy storage battery, wherein the negative electrode sheet comprises a high-capacity and fast-charge storage aromatic organic material prepared by the preparation method.

[0020] The present invention also provides a deep-sea energy storage battery, which includes the negative electrode sheet.

[0021] Principle of the present invention:

[0022] 1. Tetraaminobenzoquinone (TABQ) undergoes addition / elimination reaction under the catalysis of sodium chloride and concentrated hydrochloric acid to form intermediate oligomers with crystalline characteristics, but the conversion rate is low. After high-energy ball milling, the system is given additional reaction energy to improve the conversion rate of oligomers.

[0023] 2. After ball milling, the oligomer is heated to 300°C under vacuum conditions, and the amino and carbonyl groups undergo condensation reactions to remove ammonia and water, ultimately obtaining an aromatic organic compound with a high density of active sites and an extended conjugated structure, namely poly(pyrazine-benzoquinone) (pTAPT).

[0024] Beneficial effects of the present invention:

[0025] 1. The present invention uses tetraaminobenzoquinone (TABQ) as a synthetic monomer. An aromatic organic material with an extended conjugated structure is obtained through self-polymerization, namely, poly(pyrazine-benzoquinone) (pTAPT) organic electrode material. Since the redox site density of organic compounds is greatly improved, the conjugated skeleton of the aromatic ring is expanded and a stable hydrogen bond network is injected between molecules, the challenge of high capacity, high intrinsic ion / electronic conductivity and long-lasting cycle life in the process of organic material optimization is solved.

[0026] 2. The present invention has significant advantages such as low raw material cost, environmentally friendly process, high yield and large output, and exhibits excellent electrochemical performance. This method provides a general optimization strategy to significantly improve the energy density and cycle life of organic active materials. In the context of large-scale energy storage systems requiring excellent performance and high reliability, this high energy density, fast kinetic characteristics and durable organic electrode material shows a wide range of application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is an X-ray diffraction pattern of the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material prepared in Example 1;

[0028] In the figure, 2θ refers to the diffraction angle;

[0029] Figure 2 This is an infrared spectrum of the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material prepared in Example 1;

[0030] Figure 3 This is a Raman spectrum of the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material prepared in Example 1;

[0031] Figure 4 The molecular structure diagram of the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material prepared in Example 1;

[0032] In the figure, the parts marked in red are active sites;

[0033] Figure 5 A comparison diagram of the electron paramagnetic energy spectra of the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material and tetraaminobenzoquinone (TABQ) prepared in Example 1;

[0034] Figure 6 The poly(pyrazine-benzoquinone) (pTAPT) organic electrode material and tetraaminobenzoquinone (TABQ) material prepared in Example 1 are assembled into button-type potassium ion batteries respectively at a current density of 100 mA / g;

[0035] Figure 7The poly(pyrazine-benzoquinone) (pTAPT) organic electrode material and tetraaminobenzoquinone (TABQ) material prepared in Example 1 are assembled into button-type potassium ion batteries respectively at a current density of 1000 mA / g;

[0036] Figure 8 A comparison chart of the rate performance of button-type potassium ion batteries assembled from the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material and the tetraaminobenzoquinone (TABQ) material prepared in Example 1;

[0037] Fig. 9 The in-situ infrared spectrum of the button-type potassium ion battery assembled with the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material prepared in Example 1;

[0038] Fig.10 This is an in-situ Raman spectrum of a button-type potassium ion battery assembled with the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material prepared in Example 1.

[0039] Fig.11 The pseudocapacitance ratio of the button-type potassium ion battery assembled with the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material prepared in Example 1 at different scan rates. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand.

[0041] Example 1

[0042] A method for preparing high-capacity and fast charge storage aromatic organic materials, which uses tetraaminobenzoquinone (TABQ) as a synthetic monomer. Combined with a simple and scalable ball milling process, a subsequent in-situ thermal condensation strategy is used to obtain an aromatic organic material with an extended conjugated structure, namely poly(pyrazine-benzoquinone) (pTAPT) organic electrode material; the specific steps are as follows:

[0043] 1) Add 1 g of tetraaminobenzoquinone and 20 g of sodium chloride into an agate mortar and grind thoroughly for 15 min until a black mixture with no obvious white powder is obtained;

[0044] 2) The black mixture obtained in step 1) was added into a nylon ball milling jar with a capacity of 100 mL and filled with agate ball milling beads, and 2 mL of concentrated hydrochloric acid with a concentration of 12 mol / L was added, wherein the agate ball milling beads had particle sizes of 4 mm, 5 mm, and 6 mm, respectively, and the number ratio was 3:2:1. The ball milling jar was placed in a planetary ball mill for 10 minutes at a ball milling speed of 200 rpm to obtain a reddish brown mixture;

[0045] 3) Transfer the reddish brown mixture obtained in step 2) to a 1 L round-bottom flask, add 500 mL of 0.01 mol / L dilute sulfuric acid solution to the round-bottom flask, and heat to boil. Collect the precipitate by filtration, wash the precipitate with deionized water and anhydrous ethanol three times, put it in a vacuum oven set at 80°C, and dry it for 12 h to obtain a dark green powder;

[0046] 4) The dark green powder obtained in step 3) is transferred to a tube furnace, a vacuum environment is maintained in the quartz tube, and the heating rate is set to 5°C / min, from room temperature to 300°C. After keeping the temperature for 12 h, the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material is obtained after naturally cooling to room temperature, which is a high-capacity and fast charge storage aromatic organic material.

[0047] The performance of the prepared poly(pyrazine-benzoquinone) (pTAPT) organic electrode material was analyzed.

[0048] Figure 1 This is the X-ray diffraction pattern of poly(pyrazine-benzoquinone) (pTAPT) organic electrode material. Figure 1 As shown, the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material synthesized in the present invention has a broad and wide diffraction peak near 27°, indicating that its molecular configuration is amorphous, corresponding to π-π disordered stacking.

[0049] Figure 2 This is the infrared spectrum of poly(pyrazine-benzoquinone) (pTAPT) organic electrode material 1. Figure 2 As shown, the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material synthesized in the present invention is located at 1451 and 1239 cm -1 The new peaks (C=N, CC) at 3430 cm-1 are attributed to the newly formed pyrazine ring. The NH group at 3430 cm-1 is blue-shifted and becomes intense and broad, indicating that the π-conjugated system is expanded.

[0050] Figure 3 This is the Raman spectrum of poly(pyrazine-benzoquinone) (pTAPT) organic electrode material. Figure 3 As shown in the figure, the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material synthesized in the present invention has a high conductivity at 1388 and 1522 cm -1 They are attributed to the D peak (sp3C and bent sp2C structure) and the G peak (conjugated sp2C structure), respectively, and the ID / IG value is 0.78, indicating that it has a two-dimensional structure similar to graphene.

[0051] Figure 4 The molecular structure diagram of poly(pyrazine-benzoquinone) (pTAPT) organic electrode material. Figure 4As shown, except for the inactive amino groups at the head and tail parts, the other functional groups of the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material synthesized by the present invention are redox active and show a high active site density.

[0052] Figure 5 This is a comparison of the electron paramagnetic energy spectra of poly(pyrazine-benzoquinone) (pTAPT) organic electrode material and tetraaminobenzoquinone (TABQ). Figure 5 As shown, the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material synthesized by the present invention exhibits a more obvious Gaussian signal, which is a typical feature of the formation of cationic radicals on the nitrogen site and plays an important role in improving the conductivity.

[0053] Example 2

[0054] The button-type potassium ion battery is assembled using the high capacity and fast charge storage aromatic organic material obtained in Example 1, as follows:

[0055] (1) The poly(pyrazine-benzoquinone) (pTAPT) organic electrode material prepared by the present invention is used as a negative electrode active material for a potassium ion battery, conductive carbon black is used as a conductive agent, and carboxymethyl cellulose is used as a binder; the mass ratio of the active material, the conductive agent, and the binder is 5:4:1, and they are mixed in proportion and added with deionized water to form a slurry, which is evenly coated on a copper foil.

[0056] (2) The electrode sheet is made by punching copper foil into a 10 mm diameter disc. The mass loading of the punched electrode sheet is 0.8-1.2 mg / cm -2 .

[0057] (3) CR2016 button cells were assembled in an argon glove box; potassium metal sheet and glass fiber filter paper (GF / A) were used as the counter electrode and separator, respectively; the potassium ion electrolyte was 3 M KFSI dissolved in triethyl phosphate (TEP, 100%).

[0058] 1. In this embodiment, poly(pyrazine-benzoquinone) (pTAPT) organic electrode material and tetraaminobenzoquinone (TABQ) are respectively assembled with potassium metal electrode sheets into button-type potassium ion batteries.

[0059] Comparison of the cycling performance of two button-type potassium ion batteries at a low current density of 100 mA / g Figure 6As shown: the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material provides an initial discharge capacity of 578 mAh / g, and the capacity is 456 mAh / g after 100 cycles. However, the initial discharge capacity of the tetraaminobenzoquinone (TABQ) electrode is only 392 mAh / g, and the capacity decays rapidly to 121 mAh / g after 5 cycles. It is proved that compared with the synthetic monomer tetraaminobenzoquinone, the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material prepared by the present invention has higher actual capacity and cycle performance.

[0060] 2. Poly(pyrazine-benzoquinone) (pTAPT) organic electrode material and tetraaminobenzoquinone (TABQ) were assembled with potassium metal electrode sheets into button-type potassium ion batteries.

[0061] Comparison of the cycling performance of two button-type potassium ion batteries at a high current density of 2000 mA / g Figure 7 As shown: the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material provides an initial discharge capacity of 330 mAh / g, and the capacity is 323 mAh / g after 1200 cycles, with almost no capacity decay. However, after three pre-cycles, the capacity of the tetraaminobenzoquinone (TABQ) electrode decays significantly and has almost no capacity contribution. This once again proves that the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material prepared by the present invention has excellent cycle stability and the actual capacity is greatly improved.

[0062] 3. Poly(pyrazine-benzoquinone) (pTAPT) organic electrode material and tetraaminobenzoquinone (TABQ) were assembled with potassium metal electrode sheets into button-type potassium ion batteries.

[0063] Comparison of rate performance of two button-type potassium ion batteries Figure 8 As shown: when the current density gradually increases from 50 mA / g to 100, 200, 500, 1000, 2000, 5000 mA / g, the specific capacity of the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material is 599, 540, 484, 405, 335, 260, 171 mAh / g, respectively. When the current density returns to 50 mA / g, the capacity also returns to 575 mAh / g. The specific capacity of the tetraaminobenzoquinone (TABQ) electrode is 331, 126, 43, 15, 3.5, 1.4, 1.2 mAh / g, respectively. When the current density is 1000 mA / g, its capacity is almost 0. This shows that the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material prepared by the present invention has excellent rate performance.

[0064] 4. The in-situ infrared spectroscopy test results of button-type potassium ion batteries prepared with poly(pyrazine-benzoquinone) (pTAPT) organic electrode materials are as follows: Fig. 9As shown: These active functional groups show reversible changes in the battery electrochemical cycle, indicating that poly(pyrazine-benzoquinone) (pTAPT) organic electrode materials are stable and periodic changes in the potassium ion coordination process, with carbonyl / imine groups as potassium storage active sites. With potassiumation / depotassiumation, CO / CN changes regularly, resulting in electronic rearrangement (CC) of aromatic heterocycles / quinone rings. The charges stored on the active sites are delocalized within and between aromatic chain molecules through hydrogen bond networks, giving poly(pyrazine-benzoquinone) (pTAPT) excellent cycle stability.

[0065] The in-situ Raman spectroscopy test results of button-type potassium ion batteries prepared with poly(pyrazine-benzoquinone) (pTAPT) organic electrode materials are shown in Figure 2. Fig.10 As shown: As potassium treatment proceeds, the intensity ratio (ID / IG) gradually increases, the D peak red-shifts, and the G peak weakens. The red shift of the D peak is attributed to the enhanced CC bond stretching vibration caused by increased steric hindrance and electron density after potassium treatment. The weakening of the G peak originates from the electron redistribution of the quinone ring / pyrazine ring. After depotassium treatment, it gradually returns to its original state, further confirming the stability of the poly(pyrazine-benzoquinone) (pTAPT) organic electrode material in the cycle, and the efficient coordination reaction gives it a simple electron / ion storage mechanism, which helps to stabilize and reliable the energy storage process. 6. The test results of the pseudocapacitance ratio of button-type potassium ion batteries prepared with poly(pyrazine-benzoquinone) (pTAPT) organic electrode materials at different scan rates are shown below. Fig.11 As shown in Figure 2, when the pseudocapacitor accounts for more than 75%, it can be considered that the battery energy storage process will be dominated by fast surface charge storage, with excellent charge storage and transportation capabilities. -1 At a low scan rate of 1 mV s, the poly(pyrazine-benzoquinone) (pTAPT) organic electrode still exhibited a pseudocapacitive fraction of 74%, while the scan rate was 1 mV s -1 When the pseudocapacitance reaches 97%, it indicates that the energy storage process is completely dominated by fast charge storage, which further verifies that poly(pyrazine-benzoquinone) (pTAPT) organic electrode material is an organic material with fast charge storage capability.

[0066] The poly(pyrazine-benzoquinone) (pTAPT) organic electrode material prepared by the present invention solves the challenge of balancing high capacity, high intrinsic ion / electronic conductivity and long-lasting cycle life in the process of organic material optimization due to its high-density redox active sites and extended aromatic ring conjugated skeleton and the injection of a stable hydrogen bond network between molecules; the modification method of the organic electrode material has a simple process and high feasibility, and can realize large-scale production of high-capacity and fast charge storage aromatic organic materials, thereby promoting the practical application of high-performance potassium ion batteries, indicating that the high-capacity and fast charge storage aromatic organic materials prepared by the present invention have the potential to prepare deep-sea energy storage batteries.

[0067] Example 3

[0068] A method for preparing a high capacity and fast charge storage aromatic organic material, the specific steps are as follows:

[0069] 1) Add 2 g of tetraaminobenzoquinone and 20 g of sodium chloride into an agate mortar and grind thoroughly for 12 min until a black mixture with no obvious white powder is obtained;

[0070] 2) The black mixture obtained in step 1) was added into a nylon ball milling jar with a capacity of 100 mL and filled with agate ball milling beads, and 2 mL of concentrated hydrochloric acid with a concentration of 12 mol / L was added, wherein the agate ball milling beads had particle sizes of 4 mm, 5 mm, and 6 mm, respectively, and the number ratio was 3:2:1. The ball milling jar was placed in a planetary ball mill for 15 minutes at a ball milling speed of 200 rpm to obtain a reddish brown mixture;

[0071] 3) Transfer the reddish brown mixture obtained in step 2) to a 1 L round-bottom flask, add 500 mL of 0.01 mol / L dilute sulfuric acid solution to the round-bottom flask, and heat to boil. Collect the precipitate by filtration, wash the precipitate with deionized water and anhydrous ethanol three times, put it in a vacuum oven set at 80°C, and dry it for 12 h to obtain a dark green powder;

[0072] 4) The dark green powder obtained in step 3) is transferred to a tube furnace, a vacuum environment is maintained in the quartz tube, and a heating rate of 5°C / min is set from room temperature to 300°C. After keeping the temperature for 8 hours, the temperature is naturally cooled to room temperature to obtain a poly(pyrazine-benzoquinone) (pTAPT) organic electrode material, which is a high-capacity and fast charge storage aromatic organic material.

[0073] Example 4

[0074] A preparation method of a high capacity and fast charge storage aromatic organic material, the specific steps are as follows:

[0075] 1) Add 5 g of tetraaminobenzoquinone and 20 g of sodium chloride into an agate mortar and grind thoroughly for 18 min until a black mixture with no obvious white powder is obtained;

[0076] 2) The black mixture obtained in step 1) was added into a nylon ball milling jar with a capacity of 100 mL and filled with agate ball milling beads, and 2 mL of concentrated hydrochloric acid with a concentration of 12 mol / L was added, wherein the agate ball milling beads had particle sizes of 4 mm, 5 mm, and 6 mm, respectively, and the number ratio was 3:2:1. The ball milling jar was placed in a planetary ball mill for 10 minutes at a ball milling speed of 300 rpm to obtain a reddish brown mixture;

[0077] 3) Transfer the reddish brown mixture obtained in step 2) to a 1 L round-bottom flask, add 500 mL of 0.01 mol / L dilute sulfuric acid solution to the round-bottom flask, and heat to boil. Collect the precipitate by filtration, wash the precipitate with deionized water and anhydrous ethanol three times, put it in a vacuum oven set at 80°C, and dry it for 12 h to obtain a dark green powder;

[0078] 4) The dark green powder obtained in step 3) is transferred to a tube furnace, a vacuum environment is maintained in the quartz tube, and a heating rate of 5°C / min is set from room temperature to 300°C. After keeping the temperature for 8 hours, the temperature is naturally cooled to room temperature to obtain a poly(pyrazine-benzoquinone) (pTAPT) organic electrode material, which is a high-capacity and fast charge storage aromatic organic material.

[0079] Example 5

[0080] A preparation method of a high capacity and fast charge storage aromatic organic material, the specific steps are as follows:

[0081] 1) Add 1 g of tetraaminobenzoquinone and 20 g of sodium chloride into an agate mortar and grind thoroughly for 20 min until a black mixture with no obvious white powder is obtained;

[0082] 2) The black mixture obtained in step 1) was added into a nylon ball milling jar with a capacity of 100 mL and filled with agate ball milling beads, and 2 mL of concentrated hydrochloric acid with a concentration of 12 mol / L was added, wherein the agate ball milling beads had particle sizes of 4 mm, 5 mm, and 6 mm, respectively, and the number ratio was 3:2:1. The ball milling jar was placed in a planetary ball mill for 20 minutes at a ball milling speed of 300 rpm to obtain a reddish brown mixture;

[0083] 3) Transfer the reddish brown mixture obtained in step 2) to a 1 L round-bottom flask, add 500 mL of 0.01 mol / L dilute sulfuric acid solution to the round-bottom flask, and heat to boil. Collect the precipitate by filtration, wash the precipitate with deionized water and anhydrous ethanol three times, put it in a vacuum oven set at 80°C, and dry it for 12 h to obtain a dark green powder;

[0084] 4) The dark green powder obtained in step 3) is transferred to a tube furnace, a vacuum environment is maintained in the quartz tube, and a heating rate of 5°C / min is set from room temperature to 300°C. After keeping the temperature for 12 h, the temperature is naturally cooled to room temperature to obtain a poly(pyrazine-benzoquinone) (pTAPT) organic electrode material, which is a high-capacity and fast charge storage aromatic organic material.

[0085] Although the above embodiments have been described in detail, they are only a part of the embodiments of the present invention, not all of them. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all belong to the protection scope of the present invention.

Claims

1. A method for preparing a high capacity and fast charge storage aromatic organic material, characterized in that: The following steps are involved: (1) adding tetraaminobenzoquinone and sodium chloride into an agate mortar and grinding them thoroughly to obtain a black mixed material; (2) adding the black mixed material into a nylon ball milling jar containing agate ball milling beads, adding concentrated hydrochloric acid, and placing the nylon ball milling jar in a planetary ball mill for ball milling to obtain a mixed material; The mass volume ratio of the black mixed material and concentrated hydrochloric acid is 21-25:2, and the concentration of the concentrated hydrochloric acid is 12 mol / L; the capacity of the nylon ball mill is 100 mL; the particle sizes of the agate ball mill beads are 4 mm, 5 mm, and 6 mm, respectively, and the number ratio is 3:2:1; the speed of the ball milling treatment is 200-300 rpm, and the time is 10-20 min; (3) transferring the mixture into a round-bottom flask, adding a dilute sulfuric acid solution into the round-bottom flask, heating and boiling, collecting the precipitate, washing the precipitate, and drying at a high temperature in a vacuum to obtain a powder; The concentration of dilute sulfuric acid is 0.01 mol / L, the concentration of concentrated hydrochloric acid is 12 mol / L, and the volume ratio of concentrated hydrochloric acid to dilute sulfuric acid is 1:220-250; the precipitate is washed three times with deionized water and anhydrous ethanol; the vacuum high temperature drying conditions are 80-90°C and 8-12h; (4) transferring the powder to a tube furnace, calcining at high temperature under vacuum, and obtaining a high-capacity and fast charge storage aromatic organic material after cooling to room temperature; The heating rate of high-temperature calcination is 5°C / min, from room temperature to 300°C, and the calcination time is 8-12h.

2. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of tetraaminobenzoquinone to sodium chloride is 1-5:20; and the grinding is performed for 10-20 minutes.

3. The preparation method according to claim 2, characterized in that: The mass ratio of tetraaminobenzoquinone to sodium chloride is 1:

20.

4. The preparation method according to claim 1, characterized in that: The mass volume ratio of the black mixed material to concentrated hydrochloric acid is 21:

2.

5. A high capacity and fast charge storage aromatic organic material prepared by the preparation method of claim 1, characterized in that: The high capacity and fast charge storage aromatic organic material is prepared using tetraaminobenzoquinone as a synthetic monomer, combined with ball milling treatment, and then through a subsequent in-situ thermal condensation strategy.

6. A negative electrode sheet for a deep-sea energy storage battery, characterized in that: The negative electrode sheet comprises a high capacity and fast charge storage aromatic organic material prepared by the preparation method as claimed in claim 1.

7. A deep-sea energy storage battery, characterized in that: The battery comprises the negative electrode sheet as claimed in claim 6.

Citation Information

Cited By

  • Fused aromatic molecules as electrode materials

    US12770801B2